2008
DOI: 10.4028/www.scientific.net/amr.39-40.265
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine Containing High-Silica Glasses for Speciality Optical Fibers

Abstract: We investigated the codoping of different high-silica glasses (GeO2 – SiO2, B2O3 – SiO2) with fluorine with respect to the use of such glasses in actual optical fiber devices (fiber Bragg gratings, fiber lasers and amplifiers, optical filters, etc). It could be shown that there is a strong interaction between fluorine and the other dopants germanium and boron during gas phase deposition of the glassy layers. The doping concentration in dependence on the experimental conditions (gas concentrations, flow velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This difference is not surprising due to the different temperatures and because of the different types of glass structures. Comparing, however, the D Al value in Infrasil silica glass (≈10 − 17 m 2 /s) to the D Al value of ≈2×10 − 23 m 2 /s obtained from chemical diffusion experiments at 1000°C in a synthetic silica glass prepared by modified chemical vapour deposition [4] (after extrapolating the chemical diffusivity to negligible Al 2 O 3 concentration) one does not find any similarity. One presumably not only has to consider the different glass materials but also dissimilar diffusion mechanisms.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…This difference is not surprising due to the different temperatures and because of the different types of glass structures. Comparing, however, the D Al value in Infrasil silica glass (≈10 − 17 m 2 /s) to the D Al value of ≈2×10 − 23 m 2 /s obtained from chemical diffusion experiments at 1000°C in a synthetic silica glass prepared by modified chemical vapour deposition [4] (after extrapolating the chemical diffusivity to negligible Al 2 O 3 concentration) one does not find any similarity. One presumably not only has to consider the different glass materials but also dissimilar diffusion mechanisms.…”
Section: Resultsmentioning
confidence: 55%
“…For the impurity diffusion case an ion exchange of Al 3+ ions and e.g. Na + ions present in the Infrasil silica glass has been discussed [3], whereas in the chemical diffusion case a reaction-type mechanism between Al 3+ ions and the very pure silica host material seemed to be more likely [4]. These mechanisms clearly are different to that for Al 3+ self-diffusion in a multicomponent alumosilicate glass, where a direct isotope exchange seems to be most probable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions such as good miscibility with silica glass, glassforming, close expansion coefficient, low optical losses, availability of starting materials and reasonable dependence of refractive index on glass composition belong to basic criteria for choice of glass composition of the layers [9]. Silica doped with B 2 O 3 or fluorine exhibit lower refractive index than pure silica [10][11]. Binary or ternary systems, E.g.…”
Section: Theoreticalmentioning
confidence: 99%
“…So, there is an option to choose an operating wavelength band from the fairly wide bandwidth and the choice of material [24,25] to have an effective combination of attenuation and material dispersion. So, the challenge is to determine the best doping or fluorination combination [9,10] among the available to have the ZDW [1,2] at or near the minimum loss wavelength [26] for the optical communication systems [27,28]. As it is observed that the Wavelength Division Multiplexing and Dense Wavelength Division Multiplexing technique are among the major applications in present-day's optical communication systems.…”
Section: Introductionmentioning
confidence: 99%